Correlation Between Akt and p53 Protein Expression and Chemoradiotherapy Response in Cervical Cancer Patients - IIN KURNIA; BUDININGSIH SIREGAR; SETIAWAN SOETOPO; IRWAN RAMLI; TJAHYA KURJANA; . ANDRIONO; MARINGAN DIAPARI LUMBAN TOBING; BETHY SURYAWATHI; TEJA KISNANTO; DEVITA TETRIANA (Bogor Agricultural University, Indonesia, 2014)
Akt is a protein that is associated with cell proliferation and is expressed at high levels in cancer cells. Some research indicates it may play a role in increasing the resistance of cancer cells to chemotherapy treatment. P53 is a tumor suppressor protein that influences the cell cycle and apoptosis. The purpose of this study was to examine the relationship between the expression of Akt and p53 in cancerous tissue before chemoradiation treatment, and the clinical response to treatment of cervical cancer patients. Twenty microscopic tissue samples were taken from cervical cancer biopsies obtained from patients before cancer treatment. The tissue samples were stained with p53 and Akt antibodies via immunohistochemistry technique, to measure expression of both proteins. After completion of chemoradiotherapy, patients’ clinical response to treatment was determined using the pelvic control method. Our results revealed no correlation between expression of Akt and p53 index (P = 0.74) as well as between p53 Index and chemoradiotherapy clinical response (P=0.29). There was significant correlation between expression of Akt and cervical cancer chemoradiotherapy response (P = 0.03). There was no correlation found between p53 index and chemoradiotherapy clinical response (P = 0.29). High expression of Akt may related with high cell proliferation and resistance to chemoradiotherapy.